Serbian Early Printed Books from Venice: A Quantitative Approach to Orthographic Variations - Vladimir Polomac; Achim Rabus (Studi Slavistici)
The paper analyses the most significant orthographic variations in early printed Serbian books from Božidar Vuković's printing shop in Venice. The research was conducted based on automatically obtained transcripts using a previously trained model for automatic text recognition in the Transkribus software platform. Orthographic variations were examined at the macro level using the stylo package in the statistical programming language R, and at the micro level, by extracting the most important features of post-Resava orthography using the program AntConc. In addition to confirming the initial hypothesis that orthographic variations generally depend on the period in which the books were printed and individual printers, the paper demonstrates precise quantitative relationships of competing orthographic solutions in the corpus, which was not possible to achieve with the traditional qualitative method based on smaller text samples.